2023
DOI: 10.1038/s41598-023-32436-4
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous application of selenium and nano-selenium alleviates salt stress and improves secondary metabolites in lemon verbena under salinity stress

Abstract: Salinity stress is one of the most serious abiotic factors that affects the growth, performance, and secondary compounds of medicinal plants. The aim of this study was to determine the effect of foliar application of selenium and nano-selenium separately on growth, essential oils, physiological parameters, and some secondary metabolites of Lemon verbena under salinity stress. The results showed that selenium and nano-selenium significantly increased growth parameters, photosynthetic pigments, and relative wate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…Improving the germination quality can result in a more efficient nutrient and water uptake of seedlings, enhancing the resilience to biotic and abiotic stress 12 . Even though Se is a nonessential element for plants 47 , previous studies have reported that Se NPs can help to improve the germination, growth, and stress resilience of different crops 38 , 48 , 49 . Although the exact mechanisms of such improvements with Se NPs are still unknown, it has been proposed that the germination rate of different seeds can increase due to the NPs creating nanopores through their penetration, which consequently increases the imbibition of water by the seeds.…”
Section: Discussionmentioning
confidence: 99%
“…Improving the germination quality can result in a more efficient nutrient and water uptake of seedlings, enhancing the resilience to biotic and abiotic stress 12 . Even though Se is a nonessential element for plants 47 , previous studies have reported that Se NPs can help to improve the germination, growth, and stress resilience of different crops 38 , 48 , 49 . Although the exact mechanisms of such improvements with Se NPs are still unknown, it has been proposed that the germination rate of different seeds can increase due to the NPs creating nanopores through their penetration, which consequently increases the imbibition of water by the seeds.…”
Section: Discussionmentioning
confidence: 99%
“…The transport and absorption of several nutrients were enhanced by the exogenous application of Si (Raza et al 2019;Zia et al 2023). In the same setting, applying Se resulted in an amino acid metabolism imbalance; as a result, stressed plants exhibited higher levels of soluble protein and lower nitrate activity (Ahmad et al 2021;Ghanbari et al 2023). Similar to our ndings, the Se application also remained instrumental in protecting plant cells, increased the formation of starch in chloroplasts, and supported plant growth in salt-stressed environments (Regni et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…According to Regni et al (2021), the administration of Se enhanced olive plants' resistance to abiotic stress by preventing oxidative damage to cells and controlling their water status. Furthermore, it has been documented that the foliar application of selenium (Se) remained effective in boosting the concentration of chlorophyll in plants through the preservation of chloroplast enzymes and the augmentation of photosynthetic pigment production(Ghanbari et al 2023).…”
mentioning
confidence: 99%
“…Nano-Se alleviated salt stress by improving secondary metabolites (protein, proline, and soluble sugars) and antioxidants. [203] Red Pitaya (Hylocereus undatus)…”
Section: Before Full Flowering Stagementioning
confidence: 99%